Analisis Paralelisasi Konverter Melalui Multi Input - Single Output Transformator Frekuensi Tinggi dengan MatLab Simulink - Fitriadi Fitriadi; Valdi Rizki Yandri; Herisanjani Herisanjani (Elektron : Jurnal Ilmiah, 2020)
Two parallel converters DC/AC with isolated control can be applied by a high frequency transformer with a switching pattern. However, the switching pattern and control technique of the converter needs more research so the process of electrical energy distribution on the parallel output side can produce the optimum value. Furthermore, in this research, parallelization method is applied by utilizing two converters in high frequency transformer with multi input-single output capability controlled by Matlab/Simulink. The input side of transformer consists of two full bridge converters while secondary side represents the parallelization of output side. Two converters DC/AC is simulated by phase shifted full bridge (PSFB) of switching pattern and voltage mode control (VMC) technique. The distribution condition of optimum energy is investigated by observation of influences of ON condition duration of each switching period cycle on input converter to ON condition duration of secondary transformer terminal. The ON condition duration of each converter with switching PSFB is the condition depends on shifted/delay phase of signal on gate control. According to this simulation, optimum ON condition occurs when shifted/delay phase of each gate control signal converter is 135° (α1=α2=135°) and this condition is more efficient than phase of gate control signal is 45° (α1=α2=45°). The simulation results show that larger α of converters give the optimum distribution.